THE EFFECTIVENESS OF REALISTIC MATHEMATICS EDUCATION (RME) APPROACH TOWARD STUDENTS’ MATHEMATICS LEARNING ACHIEVEMENT OF JUNIOR HIGH SCHOOL STUDENTS - Sri Yulianti (Journal on Mathematics Education Research (J-MER), 2021)
Abstract The research aims to determine the effectiveness of Realistic Mathematics Education (RME) Model Learning of mathematics learning achievement in grade VII in SMP ba'it Al-Quran Kayuagung school year 2019/2020. This study was conducted at the Al-Quran Ba'it Junior High school year 2019/2020. This type of research is the research of pseudo experiments (quasi experiment). The sampling techniques in this study used simple random sampling techniques, the research sample was Cairo's class VII as an experimental class and the VII class of Mecca as the control class. Test instruments using this type of essay test.  Data analysis techniques with prerequisite test and hypothesis testing. Test prerequisite in the form of normality and homogenization test while the hypothesis test using parametric statistical analysis is Independent Sample T Test at the equivalent of α-significance = 0.05. The results showed that there were different learning outcomes among students who used the Realistic Mathematics approach. This is in the event of test analysis of Independent Samples T Test The value of the post test obtained significance 0.000 0.05, then H0 rejected. This means that the Realistic Mathematics Education (RME) approach is effective to improve the students’ mathematics learning achievement at SMP Ba’it Al-Quran  Kayuagung.Keyword: Learning approach, RME, Learning achievement